The Association of Fibulin-2 Expression with Histopathological Grade and Fibrotic Tumor Vessel in Meningioma - Kamelia, Muthia; Agus, Salmiah; Tofrizal, Tofrizal (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
Background Meningiomas are the most common primary tumors of the central nervous system. About one-fifth of meningiomas tend to recur. The World Health Organization (WHO) histopathological grade was the most useful morphological predictor of recurrence. Fibrotic tumor vessels (FTV) were detected in nearly half of WHO grade I meningiomas and correlated with vascular density and increased risk of recurrence. Fibulin-2 is an extracellular matrix glycoprotein whose expression increases in traumatic central nervous system injuries and can be used as a marker to differentiate the histopathological grade of meningiomas. This study aimed to determine the association of fibulin-2 expression with histopathological grade and FTV in meningiomas. Methods This research was an observational cross-sectional study. The study sample was 36 cases of meningioma in three Anatomical Pathology laboratories in West Sumatra on period January 2019 to December 2020. Samples obtained from resected meningioma cases were then reevaluated on Hematoxylin Eosin (HE) slides to determine the histopathological grade and FTV. Van-Gieson staining was performed to confirm FTV. Fibulin-2 expression in tumor cells was analyzed using immunohistochemical staining. Bivariate statistical analysis using the Chi-Square test with p<0.05 was considered significant. Result High-risk meningiomas (WHO grade II and III) showed high fibulin-2 expression (62.5%), whereas low-risk meningiomas (WHO grade I) were more abundant with low fibulin-2 expression (75%). The presence of FTV at low fibulin-2 expression was 58.3%. Statistical analysis showed no significant association between fibulin-2 expression with histopathological grade (p=0.077) and FTV (p=1,000). Conclusion In summary, the study showed that fibulin-2 expression was not associated to histopathological grade nor to FTV in meningiomas.